Factors related to physical violence experienced by parents of persons with schizophrenia in Japan. (30th September 2016) - Kageyama, Masako; Solomon, Phyllis; Kita, Sachiko; Nagata, Satoko; Yokoyama, Keiko; Nakamura, Yukako; Kobayashi, Sayaka; Fujii, Chiyo
Abstract: Most violence by patients with mental illness is perpetuated against family members rather than the general public. However, there is insufficient research to reach a consensus on factors related to family violence for this population. Thus, the current study aimed to clarify factors related to physical violence by patients with schizophrenia towards their parents in Japan. A self-administrated survey was distributed through family groups to families with a relative with a psychiatric disorder. Questionnaires completed by 400 parents of patients with schizophrenia were analyzed. Of the 400 parents, almost two-thirds experienced "no physical violence" and close to one-third experienced "physical violence" during the past year. Results of a mixed-effects logistic regression revealed that physical violence was significantly related to the patients' gender (female rather than male), multiple patient hospitalizations (3 or more times as compared to never hospitalized), low annual household income (less than US20 K as compared to over US40 K), and higher hostility and criticism of family interactions. Family violence maybe reduced through education on communication strategies for both parents and patients. Highlights: Study focused on violence by patients with schizophrenia towards their parents. 34.3% of parents experienced physical violence in the past year. High EE (hostility and criticism) related to physical violence toward parents.